Myth. Its Meaning and Functions in Ancient and Other Cultures - Kirk, G. S. (1970)
65s; esp. III (p. 84-131): The Nature of Myths in Ancient Mesopotamia: IV (p. 132-171): Nature and Culture: Gilgamesh, Centaurs and Cyclopes.